La satisfacción laboral y la rotación de colaboradores en el sector tecnológico de la Empresa Manrelec en la ciudad de Babahoyo periodo 2023. - Maldonado Coello, Nelly Anamaria (2024)
Job satisfaction and employee turnover at Manrelec has been identified as a significant challenge, associated with factors such as inadequate human resource management, lack of motivation, and job dissatisfaction. Turnover has negative consequences such as increased hiring costs and the loss of valuable talent, which impacts the company's ability to innovate and remain competitive in the technology market. The general objective of this study is to analyze the factors that influence job satisfaction and employee turnover at Manrelec, a company in the technology sector in Babahoyo during 2023. Job satisfaction is crucial for organizational performance and refers to how employees They perceive their work, influenced by aspects such as the work environment, compensation and professional development opportunities. High job satisfaction can reduce employee turnover, which is essential for maintaining the stability and operational efficiency of the company. To address these problems, a series of strategies will be implemented based on the continuous evaluation of job satisfaction through surveys and interviews. Training programs, improvements in internal communication, and adjustments to recognition and reward policies will be introduced. These measures seek to increase employee satisfaction and commitment, reduce turnover, and strengthen organizational culture. Continuous evaluation and adjustment of strategies will be key to ensuring sustainable improvements in Manrelec's work environment and, therefore, in its overall performance.